(untitled) (World Marxist Review, 2024)
Beyond critical academic-organizational roles, Cheng Enfu has been a leading representative of the Renaissance of Marxism in China during the last couple of decades. Four areas that stand out in his work are: (1) promotion of an open, critical, scientific, and innovative Marxism; (2) contributions to the labour theory of value; (3) development of the theory of the socialism with Chinese characteristics; and (4) critical exploration of contemporary imperialism.